A mountain of paper : the extraordinary diary of Leonard James Arrington - Arrington, Carl (Leonard J. Arrington Mormon history lecture series, 2012)
The series, established by one of the twentieth-century West's most distinguished historians, Leonard Arrington, has become a leading forum for prominent historians to address topics related to Mormon history. The first lecturer was Arrington himself. He was followed by Richard Lyman Bushman, Richard E. Bennett, Howard R. Lamar, Claudia L. Bushman, Kenneth W. Godfrey, Jan Shipps, Donald Worster, Laurel Thatcher Ulrich, and F. Ross Peterson. Utah State University hosts the Leonard J. Arrington Mormon History Lecture Series. The University Libraries' Special Collections and Arc.